HUBUNGAN PENGETAHUAN KEBENCANAAN DAN SIKAP KESIAPSIAGAAN TERHADAP PERILAKU ADAPTASI MASYARAKAT DALAM MENGHADAPI BENCANA TANAH LONGSOR DI KELURAHAN TAMBAKAJI KECAMATAN NGALIAN KOTA SEMARANG TAHUN 2018 INDRA HARY - Hary, Kurniawan Indra; Saptono, Putro; Ariyani, Indrayati (Geo-Image, 2018)
The purposes of this research are to determine the relationship of disaster knowledge and preparedness attitude toward adaptation behavior of society in facing landslide disaster. This research is Quantitative research. Data collection techniques used observation, interviews, tests, questionnaires, and documentation. The data analysis techniques used descriptive percentage and multiple correlation. The findingsomething of this research: the correlation analysis of disaster knowledge toward adaptation behavior obtained coefficient value equal to 0,479, preparedness attitude toward adaptation behavior obtained coefficient value equal to 0,511, disaster knowledge toward preparedness attitude coefficient number 0,429, and double correlation between disaster knowledge and preparedness attitude toward adaptation behavior obtained coefficient number of 0,586. From the research r calculated <rtabel then Ho is rejected and Ha accepted or there is relationship between disaster knowledge and preparedness attitude toward adaptation behavior of society in facing landslide disaster. Based on the Correlation Coefficient Interpretation Guidance table, the coefficient values in both research location is on moderate level of relationship. It happens because of the role factor of BPBD Semarang City that formed the disaster alert village as well as the role of the private sector in the construction of public facilities.